2011
DOI: 10.1108/17554171111155339
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence on the risk management tools practised in Islamic and conventional banks

Abstract: Purpose -The paper aims to gain an insight into the risk management tools practised in Islamic and commercial banks in Malaysia, and selected Islamic banks outside Malaysia. The study also examines the level of adequacy of risk management tools and systems of these banks. Design/methodology/approach -The study employs primary data collected using a questionnaire survey. Findings -There are significant differences in the level of extensiveness of the usage of market value at risk (VaR), usage of stress testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Furthermore, Oliveira, Rodrigues, and Craig, (2011) have proved that risk disclosure helps an organization to stabilize its operational system, market discipline effectiveness as well as sustaining the social support of the company's stakeholders. An effective risk disclosure is needed to enhance the continuous business growth and profitability (Hanim, Abdul &Omar, 2011). https://doi.org/10.15405/epsbs.2019.08.25 Corresponding Author: Fathyah Hashim Selection andpeer-review under responsibility of the Organizing Committee of the conference eISSN: 251 Risk disclosure research is widely discussed in the developed countries, yet, an interesting question is that do risk governance as important to the developing countries also (Nahar et al, 2016).…”
Section: Corporate Risk Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Oliveira, Rodrigues, and Craig, (2011) have proved that risk disclosure helps an organization to stabilize its operational system, market discipline effectiveness as well as sustaining the social support of the company's stakeholders. An effective risk disclosure is needed to enhance the continuous business growth and profitability (Hanim, Abdul &Omar, 2011). https://doi.org/10.15405/epsbs.2019.08.25 Corresponding Author: Fathyah Hashim Selection andpeer-review under responsibility of the Organizing Committee of the conference eISSN: 251 Risk disclosure research is widely discussed in the developed countries, yet, an interesting question is that do risk governance as important to the developing countries also (Nahar et al, 2016).…”
Section: Corporate Risk Disclosurementioning
confidence: 99%
“…Amran et al (2008) also proved that the stakeholders preferred the risk information to be published and disclosed in timely basis. An effective risk disclosure is needed to enhance the continuous business growth and profitability (Hanim et al, 2011). Therefore, it can be concluded that a good risk reporting and disclosure practice can lead to the better business performance of https://doi.org/10.15405/epsbs.2019.08.25 Corresponding Author: Fathyah Hashim Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 256 an organization according to the researchers.…”
Section: Hypothesis Testing For the Direct Effectmentioning
confidence: 99%
“…Additionally, the return on equity (ROE) is measured by net income over total equity of banks. The return on equity assess the financial return of a shareholder's investment and indicates how well a firm uses shareholders fund to generate profit (Tafri et al, 2011;Alper & Anbar, 2011;Saeed, 2013).…”
Section: Firm Performance Variablementioning
confidence: 99%
“…Usually, bank size is often measured by using natural log total assets and is used as a control variable in this study (Tafri et al, 2009;Akhtar et al, 2010;Athanasoglou, Brissimis, & Delis, 2008;Tafri et al, 2011;How et al, 2005). In most cases, bank size is generally used to capture potential economies or diseconomies of scale.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation